Religión, política y secularismo: Una reflexión sobre las revueltas árabes - Moya Mena, Sergio I. (2013)
This paper analyzes the various positions that exist within contemporary Islam on the relationship between religion and politics. Although a majority Orthodox stream emphasizes the inseparable relationship between politics and religion, a minority current formed by liberal theologians and scholars said that this relationship would be more historical than theological,and notes the compatibility of Islam with secularism. This debateis particularly relevant in the context of the Arab Revolts, which staked are configuration of the political systems of countries such as Morocco,Tunisia and Egypt, where the political empowerment of Islamist movement simply a much stronger role of religion in social and political life.